Customer Satisfaction in Participation Banks - Dilek, Serkan; Küçük, Orhan (Center for Strategic Studies in Business and Finance SSBFNET, 2017)
Interest income is considered as forbidden in Islam. Therefore, in Turkey, conservatives generally don’t prefer general banking and by this way funds can’t be used in economic system. So saving deficit can’t be solved in country and saving of people depreciates against inflation. Participation banks which work according to Islamic rules are set up to bring these funds to economy. Participation banking operates in more than 60 countries today and conservatives generally prefer to work with because they are working to principles of profit instead of interest. To attract and persuade more people, at first participation banks should satisfy their customers. In our study we aim to measure customer satisfaction in participation banks in Kastamonu and to reveal the differences between demographic groups. To this aim we conducted a questionnaire to customers of participation banks in Kastamonu.
Keywords: 1. No poverty; 16. Peace & justice